Penerapan Metode Make A Match Dengan Media Kantong Doraemon Untuk Meningkatkan Kemampuan Menghafal Mufradat Pada Materi Fil Maktabah Mata Pelajaran Bahasa Arab Kelas V Madrasah Ibtidaiyah Miftahul Ulum Gondanglegi - firdausi, rofiqoh; melani albar; irfan musadat (AL-WIJDÃN Journal of Islamic Education Studies, 2021)
This research was motivated by the low ability to memorize mufradat students in Arabic class V MI Miftahul Ulum Gondanglegi subjects in the 2019/2020 school year. So to overcome these problems, researchers applied the method of Make A Match with Doraemon Pockets media to improve ability to memorize mufradat students especially in the material file MaktabahThe formulation of the problem in this study is: The type of research used is Classroom Action Research (CAR) with a quantitative approach and However, about the spread of COVID-19, the research compiled cannot be carried out and in this case, it is only at the planning stage with the requirements that all research instruments must be validated. From the results of the validation carried out by 2 validators, it can be seen that the lesson plans prepared by the researchers obtained an average value of 4.5. The validation of learning media obtained an average value of 4.54. Then the written test validation (pre-test) obtained an average value of 4.19, post-test obtained an average value of 4.29. The validation on the LPP obtained an average value of 4.62 so that all the instruments prepared were suitable for use in learning.